THE DEVELOPMENT OF PROBLEM-BASED LEARNING PACKAGE BY EMPLOYING SCIENTIFIC APPROACH ON GEOMETRY SUBJECT TO GRADE X STUDENTS AT SMA - Alimin, Rismawati (Universitas Negeri Makassar, 2013)
This research is a research and development which aims The purpose of this research to develop and produce package in learning Geometry which is valid, practical, and effective. The desired product in this study is a valid, practical, and effective Geometry learning package, which consisted of 8 components, namely (1) RPP; (2) textbook; (3) worksheet; (4) test of the package; (5) observation sheet of students’ activities; (6) the observation sheet of the implementation of learning package; (7) the questionnaire of students’ responses, and; (8) validation sheet. The process of learnig package development used modification of 4-D model from Thiagarajan. The tryout was conducted at SMAN 4 Pinrang in Pinrang district to grade X MIA.2. students. The result obtained from the tryout is a valid, practical, and effective Geometry learning package. As the implications of the study, it is recommended that: (1) the Mathematics teachers should apply this package in learning Geometry, (2) for further development, teachers are expected to develop their own learning package (RPP, textbook, worksheets, and achievement test) adjusted to problem-based learning by employing scientific approach, so students will be motivated more and able to construct their own ideas/knowledge based on curriculum 2013